Caracterização, criopreservação e diferenciação in vitro de células tronco, derivadas de amniótica e gelatina de Wharton canina, visando a formação de um banco de células tronco - Arruda, Isadora [UNESP] (2014)
Mesenchymal stem cells (MSCs) are present in most of adult tissues, and are therefore attractive for cell therapy. Because of their high potential for differentiation and proliferation, they are being used in tissue reconstruction. This experiment aimed to enrich knowledge of canine MSCs derived from umbilical cord and amniotic membrane before and after cryopreservation regarding the formation of a cell bank. Thus, eight samples of amniotic membrane and eight samples of Wharton’s jelly were obtained from dogs at birth, which were subjected to enzymatic digestion and basal medium culture. Slow freezing of a sample from each culture was held at the first passage and stored for four weeks. Before and after freezing cells were subjected to characterization being observed adhesion, proliferation, differentiation and expression of surfaces markers using flow cytometry and immunocytochemistry. Based on these analyses it was demonstrated that the cells before and after cryopreservation exhibited similar behavior for proliferation and cell growth. Cell viability of amniotic membrane showed 97.0% of viable cells before freezing and 94.6% after, and the Wharton’s jelly 98.8% before and 93.5% after cryopreservation. The potential of the osteogenic and adipogênica differentiation as well as maintained, however it required a longer time (p <0.05) for the cells from Wharton's jelly to differentiate themselves after freezing. And still maintained the expression of CD44, at satisfactory levels to be considered positive, where the amniotic membrane expressed 85.6% before and 67.8% after freezing and Wharton’s Jelly expressed 86.0% before and 82.1% after cryopreservation and absence of expression of CD34 and MHC II. A peculiar feature observed was that before and after freezing spontaneous differentiation in both lineages (osteogenic and adipogenic) occurred in the controls that were not induced to differentiation. We conclude that ...